2021
DOI: 10.25103/ijbesar.142.03
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Monetary Transmission Mechanism of M&A, Greenfield FDI, Domestic Investment, and GDP Per Capita Growth: The Structural Vector Correction Model in Indonesia

Abstract: Purpose: The study aims to evaluate the different implications of mergers and acquisitions (M&A) and Greenfield foreign direct investment in the transmission mechanism effects on the growth of gross domestic product per capita (GDP per capita) in Indonesia. The origin of the study stems from past academic debates that contested whether Greenfield FDI or M&A bear more effect on the economic growth in emerging markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This means that their values have the same variance and the same mean over time. For all ports, we checked the time series stationarity using Minitab 19 (Augmented Dickey-Fuller test) and found that none of them could reject the null hypothesis (p value > 0.05) [50,51]. Additionally, through the XLSTAT 14 software, we performed both the KPSS test and the Phillips-Perron test (PP) to confirm our results [32].…”
Section: Methodsmentioning
confidence: 72%
“…This means that their values have the same variance and the same mean over time. For all ports, we checked the time series stationarity using Minitab 19 (Augmented Dickey-Fuller test) and found that none of them could reject the null hypothesis (p value > 0.05) [50,51]. Additionally, through the XLSTAT 14 software, we performed both the KPSS test and the Phillips-Perron test (PP) to confirm our results [32].…”
Section: Methodsmentioning
confidence: 72%
“…After the differences if the autocorrelation function of the time series were declining rapidly and were zero, we considered this to be a sign of stationarity. In order to determine whether the time series actually became stationary we applied the augmented Dickey-Fuller test, which had as null hypothesis that the data are not stationary (p-value <5% in order to reject the null hypothesis) (Hasudungan & Pulungan, 2021;Makatjane & Moroke, 2016). We used EViews software for this unit root test.…”
Section: Arima: Auto-regressive Integrated Moving Averagementioning
confidence: 99%